Differences in Transmission between SARS-CoV-2 Alpha (B.1.1.7) and Delta (B.1.617.2) Variants - Camino Trobajo-Sanmartín (Microbiology Spectrum, 2022)
ABSTRACT The present study aimed to compare the susceptibility and infectivity between the Alpha and Delta variants of SARS-CoV-2 and to investigate characteristics of the index case and the contact that may affect transmission. The risk of SARS-CoV-2 infection was compared between close contacts of COVID-19 cases with Alpha and Delta variants during June 2021 to August 2021. In index cases, Spike gene target failure (TaqPath) was used as a proxy of Alpha variant and the L452R mutation (TaqMan) for Delta variant. Cox regression models were used to estimate adjusted relative risks (RR). We compared close contacts of index cases with Alpha (n = 2139) and Delta variants (n = 5439). Delta variant was more transmissible overall (relative risk [RR] 1.32, 95% CI = 1.13 to 1.53), and in non-household contacts (RR 1.71, 95% CI = 1.35 to 2.16), but not in household contacts (RR 1.10, 95% CI = 0.91 to 1.34; Pinteraction < 0.001). Delta variant excess transmission was observed when the index cases were 12 to 39 years old (RR 1.51, 95% CI = 1.27 to 1.79) and the close contacts were 18 to 39 years old (RR 1.62, 95% CI = 1.29 to 2.03), but not among those younger or older than such ages. Differences in transmissibility between variants disappeared with vaccination of the index case (RR 0.68, 95% CI = 0.46 to 1.02), but not with vaccination of the close contact. This report shows that the Delta variant is more transmissible than Alpha variant mainly among young adults. Vaccination of the index cases reduced the excess transmission, which reinforces the recommendation of vaccination to reduce transmission of the Delta variant. IMPORTANCE The higher transmissibility of the Delta variant of SARS-CoV-2 in comparison with the Alpha variant has been reported. We compared the transmission of the Alpha and Delta variants by characteristics and COVID-19 vaccination status of index cases and their close contacts. Interestingly, the Delta variant showed increased transmissibility when the index case was an adolescent or young adult and when the close contact was a young adult; however, in index cases and close contacts of other age groups, transmission did not differ between variants. This may explain the increased proportion of young people who have been infected in the surges due to the Delta variant. The Delta variant was more transmissible than the Alpha variant when the index cases were unvaccinated against COVID-19, and their vaccination equaled the transmissibility of both variants, which suggests a higher impact of vaccination in controlling transmission of the Delta variant.